Extracellular vesicle sorting of α-Synuclein is regulated by sumoylation - Kunadt, Marcel; Eckermann, Katrin; Stuendl, Anne; Gong, Jing; Russo, Belisa; Strauß, Katrin; Rai, Surya; Kügler, Sebastian; Falomir Lockhart, Lisandro; Schwalbe, Martin; Krumova, Petranka; Oliveira, Luis M. A.; et al. (Acta neuropathologica, 2015)
Extracellular α-Synuclein has been implicated in interneuronal propagation of disease pathology in Parkinson’s Disease. How α-Synuclein is released into the extracellular space is still unclear. Here, we show that α-Synuclein is present in extracellular vesicles in the central nervous system. We find that sorting of α-Synuclein in extracellular vesicles is regulated by sumoylation and that sumoylation acts as a sorting factor for targeting of both, cytosolic and transmembrane proteins, to extracellular vesicles. We provide evidence that the SUMO-dependent sorting utilizes the endosomal sorting complex required for transport (ESCRT) by interaction with phosphoinositols. Ubiquitination of cargo proteins is so far the only known determinant for ESCRT-dependent sorting into the extracellular vesicle pathway. Our study reveals a function of SUMO protein modification as a Ubiquitin-independent ESCRT sorting signal, regulating the extracellular vesicle release of α-Synuclein. We deciphered in detail the molecular mechanism which directs α-Synuclein into extracellular vesicles which is of highest relevance for the understanding of Parkinson’s disease pathogenesis and progression at the molecular level. We furthermore propose that sumo-dependent sorting constitutes a mechanism with more general implications for cell biology.